SOURCES OF STRESS AMONG UNIVERSITY STUDENTS AND COPING METHODS - Jovanović, Tamara (Acta medicae Medianae, 2024)
The current literature confirms high-stress exposure in university students. That is why the aim of this study was to identify university students' self-reported sources of stress, and the most common stress coping methods. A cross-sectional study was performed to collect data on the most frequent sources of stress among university students and coping methods. The study included 309 students of the Faculty of Medicine in Foča (Bosnia and Herzegovina), 118 males and 191 females. The students rated the intensity of certain stressful situations on a scale of 1 to 10 and ranked them on an individual stress scale. The highest-ranked sources of stress were defined, and mostly they derived from non-academic sources of stress. The most common stress-coping methods were also defined. The main conclusions were that specific health promotion and stress management programs should be offered to university students in order to cope with strains during their studies.
Keywords: students, stress, health promotion